Mammillary body atrophy and other MRI correlates of school-age outcome following neonatal hypoxic-ischemic encephalopathy - Kim V. Annink; Linda S. de Vries; Floris Groenendaal; Rian M. J. C. Eijsermans; Manouk Mocking; Monique M. J. van Schooneveld; Jeroen Dudink; Henrica L. M. van Straaten; Manon J. N. L. Benders; Maarten Lequin; Niek E. van der Aa (Scientific Reports, 2021)
Abstract The mammillary bodies (MB) and hippocampi are important for memory function and are often affected following neonatal hypoxic ischemic encephalopathy (HIE). The aim of this study was to assess neurodevelopmental outcome in 10-year-old children with HIE with and without therapeutic hypothermia. Additional aims were to assess the associations between MB atrophy, brain volumes (including the hippocampi), white matter microstructure and neurodevelopmental outcome at school-age. Ten-year-old children with HIE were included, who were treated with therapeutic hypothermia (n = 22) or would have qualified but were born before this became standard of care (n = 28). Children completed a neuropsychological and motor assessment and MRI. Mammillary bodies were scored as normal or atrophic at 10 years. Brain volumes were segmented on childhood MRI and DTI scans were analysed using tract-based spatial statistics. Children with HIE suffered from neurocognitive and memory problems at school-age, irrespective of hypothermia. Hippocampal volumes and MB atrophy were associated with total and performance IQ, processing speed and episodic memory in both groups. Normal MB and larger hippocampi were positively associated with global fractional anisotropy. In conclusion, injury to the MB and hippocampi was associated with neurocognition and memory at school-age in HIE and might be an early biomarker for neurocognitive and memory problems.